Impacts of South Korea’s Political Events in 2017 Towards KRX 100 - Yusnita Octafilia; Angelina Rudyanto; Hendri . A; Sarli Rahman (Yayasan Riset dan Pengembangan Intelektual, 2021)
The capital market is a means for investors to invest in the long term and diversify, spread ownership of the company, and even create a healthy business climate through information disclosure. Political phenomena and events that occur in a country greatly affect the sensitivity of the capital market and can affect investors' decisions in investing in the capital market, because the political situation of a country affects the country's economic conditions. This study was determined of abnormal return and trading volume activity of South Korea’s political events. It has a ten windows period, amounts of samples were 98 companies of KRX 100 by purposive sampling technique. Analysis techniques used one-sample t-test and paired difference test. The result showed there is an abnormal return, a significant negative abnormal return difference, and no significant trading volume activity before and after South Korea’s political events. It means South Korea’s market is said to be efficient in a strong form because it is not influenced by political information and news that occurred in 2017.